2015
DOI: 10.4067/s0718-221x2015005000034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thinning on diameter, heartwood, density and drying defects of Gmelina arborea

Abstract: The effect of three levels thinning intensity in Gmelina arborea plantation on tree diameter, heartwood (diameter and percentage), wood density and drying defects (twist, crook, bow and check) was studied. Wood used for this study was obtained from eight-year-old plantations with thinning intensity of 60, 70 and 80% of initial density. Nine trees were selected from each trial. Results showed that tree diameter and wood density were similar in thinning intensity of 70 and 80%, but tree diameter from the plantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
7
0
3
Order By: Relevance
“…Some researchers have found that the wood density increase with age or distance from pith (Bonneman 1980, Boyce andKaiser 1961, Farmer andWilcox 1966). This is supported by the fact that the juvenile wood is usually known to be of the lower density than the mature wood (Dadswell 1958, Zobel and Buijtenen 1989, Lachenbruch et al 2011, Vallejos et al 2015. The wood density changes in the present experiment may be due to the trees which have entered the wood maturity phase and thus displayed a corresponding increase in wood density.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Some researchers have found that the wood density increase with age or distance from pith (Bonneman 1980, Boyce andKaiser 1961, Farmer andWilcox 1966). This is supported by the fact that the juvenile wood is usually known to be of the lower density than the mature wood (Dadswell 1958, Zobel and Buijtenen 1989, Lachenbruch et al 2011, Vallejos et al 2015. The wood density changes in the present experiment may be due to the trees which have entered the wood maturity phase and thus displayed a corresponding increase in wood density.…”
Section: Resultssupporting
confidence: 60%
“…Also, the higher density species tend to have stronger modulus of elasticity (low stiffness) and bending strength than lower density species (Zobel and Buijtenen 1989). Numerous studies (Johnson 1942, Dadswell 1958, Okkonen et al 1972, Zobel and Buijtenen 1989, Lachenbruch et al 2011, Vallejos et al 2015 have shown that that the shrinkage influences on wood stiffness and dimensional stability. These strong property gradients lead to warping and twisting of timber.…”
Section: Resultsmentioning
confidence: 99%
“…The thinning intensity is 70%, which has an effect on wood density and drying defects (Vallejos et al 2015). The average initial MC of the wood was above 60%, as shown in Figure 1.…”
Section: Methodsmentioning
confidence: 90%
“…Por otra parte, se observa que las propiedades físicas y energéticas de la biomasa de los clones varían principalmente por la edad, como suele suceder para G. arborea [24], [35]. Por ejemplo, el peso específico básico (Figura 1a), el poder calorífico y contenido de cenizas de fuste y ramas aumenta (Figura 2a-b, Cuadro 3) con la edad, pero en el caso de la densidad en condición verde (Figura 1b), contenido de cenizas (Cuadro 3) y cantidad de carbón (Figura 2c-d) de ramas y fuste, disminuyen con la edad.…”
Section: Discussionunclassified
“…En Centroamérica, G. arborea crece en sitios de diferente nivel de precipitación, temperatura y en suelos con niveles adecuados de calcio [23]. En el caso de Costa Rica, G. arborea es plantada en una alta variedad de sitios y el crecimiento de los árboles en plantaciones permite que en la actualidad su turno de corta sea inferior a 10 años [24]. En la producción de madera, G. arborea tradicionalmente se ha utilizado en densidades que van desde los 600-1200 árboles/hectárea con el objetivo de obtener madera para el mercado de las tarimas [25].…”
Section: Introductionunclassified